Improvement Of Teaching Material And Capacity Building On Laboratory Of Aquaculture, Fish Disease Division, Faculty Of Fisheries And Marine Science, Universitas Brawijaya - Maftuch Maftuch; Sri Andayani; Yenny Risjani; Muhammad Musa; Asus Maizar Suryanto Hertika; Febriyani Eka Supriatin; Muhammad Dailami (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
The laboratory is one of the effective learning places for students to develop scientific knowledge and skills. FPIK has 6 laboratories and 4 UPTs that can be used by students and lecturers. In practice, there are still limitations in this laboratory, including the malfunction of the equipment in the laboratory, due to damage to the equipment and the lack of mastery in operating the tools. This community service is intended to help solve problems that exist in the Aquaculture Laboratory of the Fish Disease Division of FPIK UB by increasing the capacity of human resources and laboratories in testing services. The form of service activities carried out includes organizing online workshops on fish hematology and histology testing, making learning videos for practicum analysis of fish hematology, developing collaboration networks with other laboratories, adding laboratory testing instruments and packages and cooperation in scientific publications.